Africa RISING-Intensification of Livestock Forage Rations - International Livestock Research Institute (International Livestock Research Institute, 2015)
Good dairy cattle feeding management practices must be followed to achieve maximum performance from cows. A 4% increase in feed utilization can be expected when using a total mixed ration (TMR) compared to conventional ration of forage and grain fed separately, twice daily. In addition, the ability to use feeds with various rates of breakdown is enhanced, often enabling even better nutrient utilization. Farmers can also utilize a greater variety of byproduct feeds with a TMR, thereby allowing for possible ration cost savings. The incidence of digestive and metabolic problems often decreases when a TMR is fed, and milk production has been shown to be as much as 5% higher with a TMR compared to conventional rations as a result of these benefits. This paper discusses sustainability perspectives of intensification of TMR?s compared to conventional feeding among small holder farms in Babati district, Tanzania. Our analysis suggests that smallholder farmers will benefit from reduced feed wastage due to increased palatability of TMR?s as well as increased milk yield and income. Trade-offs are that despite the significant time and effort spent formulating total mixed rations, it is evident that feed utilization and milk production will be increased and consequently feed cost reduced. To learn more about this dataset, please visit ILRI Datasets Portal http://data.ilri.org/portal/dataset/africa-rising-intensification-of-livestock-forage-rations